Effect Of Pressure And Droplet Number On Smt Adhesive Dispensing - Yusoff, Nur Maisara Mohamed (Universiti Sains Malaysia, 2019)
Automatic dispensing machine is used to help the process of dispensing adhesives on the PCBs. Time-pressure (contact) dispensing method is the most common method used in industry, due to its flexible and easy maintenance. Adhesive dots are generally used to hold certain components onto the PCB during the wave soldering process. Thus, this project will determine the best pressure and droplet number of adhesive dispensing using Computational Fluid Dynamic (CFD) in ANSYS Fluent software. In time pressure dispensing, an air supply connected to a syringe is used to provide compressed air in fixed pulses to push the adhesive out through the needle or nozzle of the syringe. The adhesive must be choosen carefully to make sure it is strong and have sufficient attachment capability, to hold the components in place until cured. From all the simulations, one droplet dispenser with a pressure of 290000 Pa showed the best result.